Progress in Relativity - Gheorghe Buzea, Calin; Agop, Maricel; Butler, Leo; Gheorghe Buzea, Calin; Agop, Maricel; Butler, Leo (IntechOpen, 2020)
This volume deals with extensions of special relativity, general relativity, and their applications in relation to intragalactic and extragalactic dynamics. The book comprises chapters authored by various researchers and edited by an expert active in the relativity research area. It provides a thorough overview of the latest research efforts by international authors on relativity, opening new possible research paths for further novel developments.
English
Keywords: Particle & high-energy physics; Quantum physics (quantum mechanics & quantum field theory)